Sex‐related differences in abdominal obesity impact on ischemic stroke risk. (29th December 2016) - Rodríguez‐Campello, A.; Jiménez‐Conde, J.; Ois, Á.; Cuadrado‐Godia, E.; Giralt‐Steinhauer, E.; Vivanco, R. M.; Soriano‐Tárraga, C.; Subirana, I.; Muñoz, D.; Gómez‐González, A.; Puig‐Pijoan, A.; Roquer, J.
Abstract : Background and purpose: The objective of our study was to evaluate sex differences in the impact of weight and abdominal obesity on the risk of ischemic stroke. Methods: We included 388 patients with ischemic stroke (aged <75 years) assessed consecutively in our hospital and 732 controls matched by age and sex. Vascular risk factors and anthropometric data (waist circumference, weight and height) were recorded. The impact of three anthropometric variables [body mass index (BMI), waist circumference and waist to height ratio] on ischemic stroke risk was calculated. These variables were divided into quartiles for a comprehensive comparison between cases and controls, stratified by sex and adjusted in logistic regression by age and vascular risk factors. Further logistic regression using dummy variables was performed to evaluate the association between BMI‐adjusted abdominal obesity and stroke risk. Results: Increased BMI was not associated with increased stroke risk overall or in women, but was a protective factor in men [ P = 0.03; odds ratio (OR), 0.59 (0.37–0.94)]. Abdominal obesity was a risk factor for stroke in women, in both waist circumference [ P < 0.001; OR, 5.79 (3.10–10.85)] and waist to height ratio [ P < 0.001; OR, 3.61 (1.99–6.54)] analyses, but was not significant in men. When considered independently of BMI, abdominal obesity was a risk factor in both sexes, but the strength of the association was significantly higher in women. Conclusions: Increased BMI was related to a lower risk of stroke in men. Abdominal obesity was associated with ischemic stroke in women. The impact of abdominal obesity on stroke risk differs by sex.